IDENTIFIKASI GARIS BATAS CITRA HILAL MENGGUNAKAN KERNEL MATRIKS - Agus Andreansyah (Universitas Islam Nahdlatul Ulama Jepara, 2023)
IDENTIFICATION OF HILAL IMAGE BOUNDARIES USING MATRIX KERNELDetermination of worship times, especially the months of Ramadan, Shawwal, and Dzulhijah based on the sighting of the new crescent (first crescent) after sunset. The sighting of the hilal is sometimes problematic because it is often invisible or the hilal has decreased in quality (degradation) as happened in the Bangka Belitung Islands Province during monitoring to determine the beginning of Ramadan 1443 Hijriah. Thus, it is necessary to have a process for improving the hilal image to make it easier to identify or detect the clear, strong, and thick hilal boundary line. The processing of the new moon image starts from the process of changing the RGB image to a grayscale image which will make it easier to determine the new moon boundary line using the matrix kernel operators, namely roberts, prewitt, sobel, and canny. After applying the four operators, then the image is processed by thresholding segmentation to sharpen the image boundaries and separate objects from the background in an image based on their brightness or darkness. The test results of the four matrix kernel operators that were applied to the visible hilal image and the degraded hilal image showed that the prewitt and sobel operators had the best level of performance in detecting or identifying clear boundary lines. Meanwhile, the operator roberts is also able to detect the boundary line of the new moon image, but it is a bit thin and blurry. Unlike the case with the canny operator, which cannot detect it properly and cannot directly separate the object from the background.